The Role of Nurse in the Form of Palliative Care on the Quality of Life of Patients with Cervical Cancer - Rita Kirana; Tut Barkinah; Vonny Khresna Dewi (Aloha International Journal of Health Advancement (AIJHA), 2020)
The diagnosis of cervical cancer has become a big burden for both patients and families. Most patients with advanced stage cancer have a low quality of life score which indicates they have a problem. while the family may not be ready to carry out its role in the quality of life of patients with cervical cancer. The objective of this research was to identify the correlation of nurse support in the form of palliative care on the quality of life of patients with cervical cancer. This research employed cross-sectional design. Population in this research was all patients with cervical cancer in gynecology ward in Banjarmasin. Participant for this research were patients with cervical cancer and nurses. Data were taken by structured interview and task question form. Linear regression analysis was applied with level of significance ≤0.05. The results shown that most nurses ha good level of their role in the form of palliative care while most patients also have moderate level of quality of life. Also there are significance correlations of nurse role in the form of palliative care on the quality of life of patients with cervical cancer. Keywords: cervical cancer; quality of life; palliative care; nurse; role